BIOACTIVE MARINE-DERIVED COMPOUNDS AS POTENTIAL ANTICANCER CANDIDATES - S Ellithey, Mona; H Ahmed, Hanaa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to evaluate for the 1st time the anticancer activities of sarcophytol M (1), alismol (2), alismoxide (5), 7Î²-acetoxy-24-methylcholesta-5-24(28)-diene-3,19-diol (7), erythro-N-dodecanoyl-docosasphinga-(4E,8E)-dienine (8), and 24 methylcholesta- 5,24(28)-diene-3Î²,7Î²,19-triol (9). Compounds were isolated from the soft coral Lithophyton arboreum and tested in liver (HepG2), lung (A549), and breast (MDA) cancer cell line. Methods: Anticancer activities of the compounds were tested using (XTT) 2,3-bis-(2-methoxy-4-nitro- 5-sulfophenyl)-2H-tetrazolium-5-carboxanilide, Na2) in vitro assay in order to estimate the cytotoxicity and to determine the IC50s. The free radical scavenging activity of the compounds were measured by 1,1-diphenyl-2-picryl-hydrazil (DPPHâ€¢). All compounds were screened at 100 Î¼g/ml while the most potent active compounds were assayed at lower concentrations. Results: Compounds (7) and (9) showed a strong cytotoxic effect with IC50 of 6.07, 8.5 Î¼g/ml in HepG2, 6.3, 5.5 Î¼g/ml in MDA cells, and 5.2, 9.3 Î¼g/ml in A549 cancer cell lines, respectively. In addition, moderate cytotoxicity was shown by compound (2) (IC50 16.5, 15, and 13 Î¼g/mL) in HepG2, MDA, and A549 cancer cell lines, respectively. Conclusion: The results obtained in this research work indicated a promising potential cytotoxicity of compounds (7) and (9) compared to its safety margins in Vero cells, and the expected cytostatic effect of compound (2) can be used in drug cocktails for the treatment of the major cancer types’ lung, breast, and liver cancer. Â